Proteomic sensing associated with terpenoid biosynthesis of Artemisia annua L. in response to different artificial light spectra - Darunmas Sankhuan; Sittiruk Roytrakul; Masaru Nakano; Kanyaratt Supaibulwatana (Journal of Plant Interactions, 2022)
Artificial light has been used to control plant growth and secondary metabolite production. Artemisia annua L. plants were illuminated with three light-emitting diode (LED) spectra to investigate proteomic and biochemical responses. After 7 days, proteomic data revealed different protein numbers in leaves, stems, and roots under particular treatments. Results demonstrated increased accumulation of several proteins, including secondary metabolite-related proteins. The red light (R) (660 nm) highly induced terpenoid proteins. Similar biochemical profiles were observed in white light (W) (445, 544 nm) and blue light (B) (445 nm) conditions, while profiles from R treatment were different. Functional proteins of W and B treatments were involved in the MVA and MEP pathways and sesquiterpene biosynthesis. By contrast, unique proteins in R treatment were mainly expressed in sesquiterpene and tetraterpene biosynthesis. Specific relationships between biosynthetic proteins and sesquiterpenes were observed, suggesting the indispensable role of the light spectrum in regulating terpenoid biosynthesis.